MODERN REQUIREMENTS FOR PRIMARY EDUCATION AND THEIR MAIN TASKS (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
In this article, views and considerations are presented regarding modern requirements in the primary education system and their main tasks. It discusses the changing conditions of our country’s education system, as well as the influence of globalization and digital technologies. The importance of modern pedagogical approaches, innovative teaching methods, and learner-centered education in primary schooling is highlighted.